Luminescent supramolecular polymer nanoparticles for ratiometric hypoxia sensing, imaging and therapy. (24th August 2018) - Huang, Yuan-Yuan; Tian, Ye; Liu, Xiao-Qin; Niu, Zhongwei; Yang, Qing-Zheng; Ramamurthy, Vaidhyanathan; Tung, Chen-Ho; Chen, Yu-Zhe; Wu, Li-Zhu
Abstract : The first example of a multi-functional supramolecular polymer-based nanoprobe for ratiometric hypoxia sensing, imaging and PDT treatment is reported. Abstract : Hydrogen-bonded supramolecular polymer nanoparticles (SPNPs), serving as a ratiometric oxygen nanoprobe for hypoxia sensing and photodynamic therapy (PDT) treatment, were designed. Herein, oxygen-sensitive phosphorescent Pt(ii ) porphyrin moiety and oxygen-insensitive fluorescent 9, 10-diphenylanthracene moiety were assembled through quadruple hydrogen bonding into SPNPs. The efficient energy transfer between the monomeric donor–acceptor pairs in the SPNPs leads to enhanced phosphorescence with long lifetimes. The resulting bright phosphorescence can realize hypoxia sensing in living cells and generate singlet oxygen efficiently in SPNPs to kill cancer cells. This is the first example of a multi-functional supramolecular polymer-based nanoprobe for ratiometric hypoxia sensing, imaging and PDT treatment.